PRINCIPLE OF STATE ADMINISTRATION IN UKRAINE: TRANSFORMATION TO MODERN TERMS - Орлов, Николай (Modern engineering and innovative technologies, 2017)
The considered principles of state administration in Ukraine and their transformation are to the modern terms. Principles of openness of state administration are given. The analysis of scientific works is conducted after this subjects. Certainly direction